UMPSA researcher, Professor Ir. Ts. Dr. Kamarul Hawari, develops iSenseFishery, AI-Based Aquaculture Management System - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 22 January 2025 – It is widely known that the aquaculture industry is among the largest contributors to the seafood industry.